Islam and Traditional Fabrics: Symbolic Da’wah in Sambas Malay Weaving Motifs, West Kalimantan - Harles Anwar; Mualimin Mualimin; Faras Ramadhan Fauzan; Alkadri Alkadri; Zaenal Mukarom; Abbas Muhammed Zakariya (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
This article aims to analyze symbolic da'wah through the weaving motifs of Malay Sambas, West Kalimantan. This study uses an interpretive paradigm with a semiotic method. The data sources in this study were 22 motifs of Sambas Malay woven fabric. Data was obtained through observation and interviews. The data obtained were then analyzed using the semiotic triangle meaning model of Charles Sander Peirce. This study finds that the woven fabric motif is formed through a long process and closely relates to the socio-cultural construction of the Sambas Malay society. At this level, the Sambas Malay weaving motif is created from three elements: beauty, cultural identity, and the ethnoreligious reality of the Sambas Malay society, and efforts to internalize Islamic teachings in Sambas Malay life through the meaning and symbolic message of the motif. Based on these findings, it can be concluded that the Sambas Malay weaving motif is not only a cultural product of the Sambas Malay society but also a symbolic da’wah medium in the Sambas Malay society through a cultural approach.